Localized microstructural characterization of a dissimilar metal electron beam weld joint from an aerospace component - Sathiskumar Jothi (Materials & Design, 2016)
HICC and HE are known to cause failures in aerospace components. Hydrogen embrittlement (HE)and Hydrogen induced cold cracking (HICC) are influenced by the local misorientation, microstructural evolution, recrystallization of grains, residual plastic strain and the resultant grain boundary characteristic distribution (GBCD) brought about by welding processes. It is vitally important to quantify the microstructural evolution, degree of residual plastic strain and determine the GBCD across dissimilar weld joints in order to assess the susceptibility of the weld joint to these phenomena. In this investigation a full microstructural characterization study was carried at various locations within and around a dissimilar weld joint of Pulse-plated Nickel and Inconel 718, taken from an aerospace component. Areas examined included the base metals, weld fusion zone and heat affected zones on both side of weld dissimilar joints, formed via electron beam welding. Scanning electron microscopy/electron backscattering diffraction was employed to measure the crystal orientation distribution, grain size distribution,, misorientation distribution, residual plastic strain, grain structure, GBCD of the dissimilar weld joint. Metallurgical examination was carried out using SEM on HAZ in IN718 to investigate the secondary phase precipitates due to welding process.